Security and Protection in Information Processing Systems IFIP 18th World Computer Congress TC11 19th International Information Security Conference 22–27 August 2004 Toulouse, France - Deswarte, Yves; Cuppens, Frederic; Jajodia, Sushil; Wang, Lingyu (IFIP Advances in Information and Communication Technology, 2004)
Security is probably the most critical factor for the development of the "Information Society". E-government, e-commerce, e-healthcare and all other e-activities present challenging security requirements that cannot be satisfied with current technology, except maybe if the citizens accept to waive their privacy, which is unacceptable ethically and socially. New progress is needed in security and privacy-preserving technologies. On these foundations, the IFIP/SEC conference has been established from the eighties as one of the most important forums for presenting new scientific research results as well as best professional practice to improve the security of information systems. This balance between future technology improvements and day-to-day security management has contributed to better understanding between researchers, solution providers and practitioners, making this forum lively and fruitful. Security and Protection in Information Processing Systems contains the papers selected for presentation at the 19th IFIP International Conference on Information Security (SEC2004), which was held in August 2004 as a co-located conference of the 18th IFIP World Computer Congress in Toulouse, France. The conference was sponsored by the International Federation for Information Processing (IFIP).This volume is essential reading for scholars, researchers, and practitioners interested in keeping pace with the ever-growing field of information security